Impact of body mass index on outcomes of laparoscopic radical prostatectomy with long-term follow-up. (February 2015) - Gözen, Ali Serdar; Akin, Yigit; Özden, Ender; Ates, Mutlu; Hruza, Marcel; Rassweiler, Jens
Abstract Objective. The aim of this study was to investigate the impact of body mass index (BMI) on the functional and oncological results of patients who had undergone laparoscopic radical prostatectomy (LRP). Material and methods. In total, 1224 patients with follow-up data (>24 months) were enrolled. Patients were divided into three groups according to BMI (kg/m2) as: group 1 (normal, BMI <25, n = 425), group 2 (overweight, 25 ≤BMI <30, n = 594) and group 3 (obese, BMI ≥30, n = 205). Demographic, intraoperative and postoperative data with oncological outcomes were recorded. The impact of obesity on those parameters was evaluated and statistical analyses were performed. Results. Mean age was 63.8 ± 6.1 years and mean follow-up was 43.1 ± 25.1 months (mean ± SD). There were 425 (34.7%) patients in group 1, 594 (48.5%) in group 2 and 205 (16.8%) in group 3. Operation time, clinical stage and estimated blood loss were significantly higher in group 3 than in the other groups (p < 0.001, p = 0.001 and p = 0.001, respectively). Bilateral nerve-sparing rate and bladder neck-sparing rate were significantly decreased in group 3 compared with the other groups (p = 0.001 and p < 0.038, respectively). Statistically significantly higher pathological stage, tumour volume, positive surgical margin and Gleason scores were determined in group 3 compared with the other groups (p = 0.023, p = 0.018, p = 0.009 and p = 0.028, respectively). There were similar urinary continence rates among the groups. The rate of penetration with or without medication was significantly lower in group 3 than in the other groups (p = 0.593 and p = 0.007, respectively). Conclusions. LRP seemed safe and effective in obese patients, with similar mean overall survival, cancer-specific survival, complication rates and continence rates to normal weight patients in the long term.